Cadmium transcriptionally regulates Scd1 expression in silver pomfret. Issue 3 (18th November 2019) - Shi, Peng; Meng, Ran; Liao, Kai; Li, Shuang; Hu, Jiabao; Xu, Jilin; Zhang, Lin; Cao, Jiayi; Ran, Zhaoshou; Wang, Danli; Xu, Shanliang; Wang, Yajun; et al.
Abstract: Cadmium (Cd) is one of the major contaminants in aquatic ecosystem. Stearoyl‐coenzyme A desaturase 1 (Scd1) has been implicated in adaptive responses to environmental stressors. The objectives of this study are (a) to characterize scd1 mRNA from silver pomfret ( Pampus argenteus ); (b) to investigate the expression and activity of Scd1 in silver pomfret exposed to Cd; and (c) to investigate how Cd modifies scd1 gene transcription in silver pomfret. Results indicated that Scd1 was generally conserved across fish species and scd1 mRNA level was higher by far in the brain and liver, followed by the kidney and intestine. Exposure to Cd led to significant changes of the expression and activity of Scd1 in in the liver and intestine. The liver mRNA abundance of scd1 was significantly lower in the Cd‐treated groups than in the control group. The 10 days treatment with 1 mg/L Cd significantly upregulated the intestinal scd1 mRNA level, an approximately 9‐fold higher in the 1 mg/L Cd‐treated group as compared with the control group. Accordingly, Scd1 activity indices (18:1n‐9/18:0) in the liver were significantly decreased in the 0.5 mg/L group compared with the control group, while Scd1 activity indices in the intestine were significantly increased in the 1 mg/L group compared with the control group. Moreover, overexpression of sterol regulatory element binding transcription factor 1 (Srebp1) and peroxisome proliferator–activated receptor γ (Pparγ )in HEK 293T cells produced a 2‐fold increment in the activity of the scd1 promoter. Furthermore, srebp1 had a similar expression pattern to scd1 in the liver and intestine of silver pomfret exposed to Cd. These results indicated that Cd could regulate scd1 expression, possibly through the transcriptional factor Srebp1.